Field test results for space-time coding - Gupta, P.; Weijun Zhu; Fitz, M.P.; Heechoon Lee; Liu, D.N.; Wong, S.W.G. (2003 37th Asilomar Conference on Signals, Systems and Computers, 2003)
Multiple antenna radios are recently the subject of much research due to the significant improvements they offer in throughput and reliability in wireless communications. Research in the field of space-time coding has led to the design of modulation techniques offering improved performance. Their performance, although promising in simulations, needs to be studied in real wireless channels due to the inability to accurately model all possible wireless channel conditions that might be seen in practice. With this motivation, a range of experiments were conducted to measure the performance of some of the well-known space-time codes in literature over real channels and under implementation impairments. This paper discusses the testbed setup for the experiments and present the results of field trials conducted at the University of California, Los Angeles.